Difference in association. About bridging the cultural gap when translating Ibsen's En folkefiende - Peters, Anne Lande (Nordlit, 2015)
Ibsen-In-Translation aims at translating Ibsen’s work simultaneously into the languages of: Classic Arabic, Chinese, Egyptian, English, Hindi, Japanese, Russian and Spanish. During the translation of En Folkefiende the group met twice to discuss problems and help eachother’s understanding of the play. This article aims at pointing out some of the common translation-problems the eight translators encountered, and to mention specific problems I encountered in the process of translating the play into Japanese.During our two meetings, I saw that some problems were language-specific, and that some were common to more of us. We also discovered that some words and expressions are so rooted in the Norwegian culture and that a literal translation of such words and expressions create different associations in the target language. Among the problems we had in common, there seemed to be two main categories. 1: Concepts related to Christian values, and 2: Concepts related to the Norwegian societal organization of the time. Christian values-related problems consisted of translating swearwords, translating the concepts and the associations related to the words ”temperance”, ”atheism” and ”openmindedness”. As for the problems relating to societal organization and political ideology in Norway of the time, concepts relating to the term ”borger” was a challenge for many of us. As for me specifically, I also had the added challenge of fitting the relatively democratic language of Ibsen into the Japanese hierarchical language system.
Keywords: Ibsen in Translation; Japanese; En folkefiende / An Enemy of the People; Cultural gap; Translation problems; Swearwords; Hierarchy in language